Inovasi Teknologi dalam Industri Kecantikan: Penerapan Sistem E-Commerce pada Shine Nature - Ria Juliana; Indah Refiana; Bintang Ermanda Arya Putra (Lembaga Pengembangan Kinerja Dosen, 2025)
Shine Nature, a company engaged in beauty products and services, is the subject of this research. The aim of this research is to create a web-based e-commerce system that will assist in the digitalization of the company's sales processes. The Waterfall method, software engineering approach, and Unified Modeling Language (UML) diagrams are used to describe the flow and structure of the system. With this design, features for managing product data, care services, customers, transactions, and sales reports have been integrated and organized in a database. Customers can also order goods and services online through the system. This system makes the business management process more effective, accurate, and usable anytime and anywhere. This system is expected to be a digital solution that helps UMKM enhance their competitiveness in the era of digital transformation.